Long Non-coding RNAs Gabarapl2 and Chrnb2 Positively Regulate Inflammatory Signaling in a Mouse Model of Dry Eye - Yang, Yuhan; Chen, Minjie; Zhai, Zimeng; Dai, Yiqin; Gu, Hao; Zhou, Xujiao; Hong, Jiaxu (Frontiers in Medicine, 2021)
Purpose: To elucidate the expression profile and the potential role of long non-coding ribonucleic acids (RNAs; lncRNAs) in a dry eye disease (DED) model. Methods: A DED model was established in C57BL/6J mice with 0.2% benzalkonium chloride (BAC) twice a day for 14 days. The differentially expressed lncRNAs were detected by RNA-seq technology and the aberrantly expressed lncRNAs were further verified by RT-qPCR. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were conducted to predicate the related candidate genes and potential pathological pathways. Cells from a human corneal epithelial cell line (HCECs) were cultured under hyperosmolarity. The regulation of inflammatory factors by silencing potential targeted lncRNAs was verified in vitro in HCECs. Results: In our study, a significant increase in corneal fluorescence staining and a reduction in tear production were observed in DED mice at all follow-ups compared with the controls, and the differences were increasing over time. In total, 2649 upregulated and 704 downregulated lncRNAs were identified in DED mice. We selected six aberrantly expressed and most abundant lncRNAs and performed RT-qPCR using the samples for RNA-seq. Chrnb2, Gabarapl2, and Usp31 were thereby confirmed as the most significantly altered lncRNAs. Pathway analysis revealed that the neuroactive ligand–receptor interaction signaling pathway was the most enriched, followed by the calcium signaling pathway and cytokine–cytokine receptor interaction. Following treatment of Gabarapl2 siRNA and Chrnb2 siRNA, tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and interleukin (IL)-6 were significantly downregulated in the HCECs. Conclusion: Our study suggests that Chrnb2 and Gabarapl2 may be involved in the inflammation response by regulating TNF-α, IL-1β, and IL-6 in DED. These candidate lncRNAs may be both potential biomarkers and therapeutic targets for DED.